Film noir production the whodunit of the classic American mystery film - Landau, David 1956- (Routledge, 2017)
"David Landau's Film Noir Production: The Whodunit of the Classic American Mystery Film is a book meant for those who like a good story, one the Noir Films always delivered, concentrating on the characters more than anything else. Readers will find in these pages many behind-the-scenes tales of the productions of certain hard-boiled film classics and the prime players involved in their creation, from Darryl Zanuck and Raymond Chandler to John Seitz and Billy Wilder. This book features: -A clear understanding of how movies are actually made and all the creative artists that contribute, creating a better appreciation for the many talented artistic collaborators that worked in the Hollywood Studio System and who together created film noir; -A behind-the-scenes look at the making of a classic film noir movie that typifies the chapter's subject, allowing the reader to view that film in a new light and think about it from a new prospective; -Appendices of suggested films to screen, film noir books for further reading, and downloadable files containing discussion points and class assignments for each chapter; -An informative and conversational writing style, making the subject matter easy to digest and fun to read. This book is an indispensable companion text for anyone studying or interested in film noir, film history, the bygone days of the Hollywood film factories or how movies are actually made"--Provided by publisher
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Film noir -- History and criticism -- United States; Films noirs; États-Unis; Histoire et critique; PERFORMING ARTS; Reference; PERFORMING ARTS; Film & Video; History & Criticism; PERFORMING ARTS; Film & Video; Reference; Film noir; United States; Criticism, interpretation, etc